Biogas Production through Co-Digestion of Olive Mill with Municipal Sewage Sludge and Cow Manure: 10.32526/ennrj/20/202100162 - Al Rabadi, Said; Al-Zboon, Kamel; Shawaqfah, Moayyad; Damseh, Rebhi; Al Zoubi, Omar (Environment and Natural Resources Journal, 2022)
The treatment of olive mill (OM) residues from agricultural facilities is a daunting challenge since tremendous amounts are disposed per annum that should be treated. One of the promising treatment methods is the anaerobic methanogenic digestion of OM residues. In current investigations, the anaerobic digestion of the OM substrate is enhanced through mixing its slurries with sewage sludge (SS) or with cow manure (C), which consists of the kernels for the digestion process. Besides feedstock, other operational parameters such as hydraulic retention time (HRT), temperature and pH have a great impact on the biogas production rate and quality. Experimental investigations were conducted by means of the anaerobic biodegradation of the substrate for OM-SS and -C using a batch reactor under mesophilic conditions and foreseen HRT for 30 days. Almost neutral pH values of 7.4-7.6 were found for the anaerobic treatment of the substrate for OM-SS, and a slightly acidic pH in the range of 4.8-5.3 was found for the anaerobic treatment of the substrate for OM-C. The results revealed that the biogas production for OM-SS and -C exceeded 0.07 and 0.31 LBiogas/(LFerm·day), respectively. Regarding the COD reduction, its removal efficiency was obtained as 46.1 and 53.8% for OM-SS and -C respectively. For economic concerns, significant methane yields were attained as 56.8 and 115.8 [LCH4/kgCOD] for the OM-SS and -C substrates, respectively. In virtue of these remarkable merits, anaerobic methanogenic digestion should be adapted to a commercial scale for the treatment and biogas production of OM residues.